Alteridade e diálogo: uma meta-arqueologia da educação a partir de Emmanuel Lévinas e Paulo Freire - Guedes, Edson Carvalho (2007)
The meta-archeology of Education, suggested in this work, refers to Emmanuel Lévinas and Paulo Freire and wants to orientate a philosophical reflection about the questions raised by the necessity of looking at the Other as a source of learning that enables the human being to be more. The problem concerning this research may be explained as follows: How can Lévinas Philosophy, in a dialog with the educational Theory by Paulo Freire, help defining principles or bases of intersubjective relationships present in education? We consider that the intersubjective relationships, within the educational universe, are built over two great bases or over a basis properly defined and over something that is beyond the basis. A contribution that this research brings and that reveals a possible originality within the educational field refers to the deconstruction of the category that is conveniently referred to as basis or principle. Supported by the philosophy of Emmanuel Lévinas, we present a perspective concerning the Western philosophy that comprised, most of the times, totalitarian bases, concerned about the unit, coherence and synthesis, dismissing, because of that, the singularities, the contradictions and the diversities. We suggest the term meta-archeology to indicate a reality that begins, but that is open to diversity, the difference, resistant to presenting itself as a paradigm. The hypothesis that determined the beginning of our works, already influenced by the philosophy of Emmanuel Lévinas and by the epistemology of the education of Paulo Freire, brings as an answer to our thesis problem the following statement: The relationship between the alterity and the exercise of the dialog enable and emphasize a metaarcheology of the emancipative education, beyond the identity limits. On the other hand, it is the autological rationality that begins and sustains, within the educational processes, the interpersonal relationships excluding and resistant to diversity. In order to build a methodology that would organize the approach of a subject in regards to a phenomenon and, at the same time, offer sufficient elements to [dis]organize and [re]organize the speech in view of future theoretical and practical constructions, we considered it is more convenient to approach the questions raised by the phenomenological hermeneutics of Paul Ricoeur. The thesis was grounded on four main categories: knowledge and autology, on the one hand, and alterity and dialog on the other hand. These are two cuts that tension each other reciprocally. The comprehension of the first group of categories favors the comprehension of the second one and vice-versa. The first group is understood as the basis or principle for the education; the second one, as meta-archeology, something that is beyond the principle (arché). The set of Lévinas categories has alterity as its central category and articulator of the others: ethics and philosophy first, language, subjectivity, autrement (different than being). The set of Freire categories has dialog as its central category and articulates the others: freedom, social and political, justice, culture. With these categories, we tried to build an educational theory that may enable ethical learning processes of reception and commitment with others and even enable learning for the suspicion, refractory to the will of power.